The Green synthesis of gold nanoparticles from synephrine extracted of citrus auriantum and its Potential effect against dermatophytes in vitro - Ayat Subhi Jadou,; Rusol,M Albahrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The prevalence of skin infections caused by fungi, especially dermatophytes species, has been on the rise recently. Patients with impaired immune systems are at increased risk for these infections, and the prospect of medication resistance is a real worry due to the current pharmacological landscape. Hence, new antifungal medications are required. Synephrine, a chemical with antibacterial and antifungal characteristics, was isolated from citrus sinensis peels. In order to verify the presence of synephrine, the extract was examined using thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). A green synthesis approach was also employed to produce gold nanoparticles (AuNPs) using the extract. Energy dispersive spectroscopy (EDS), field-emission scanning electron microscopy (FESEM), and ultraviolet-visible spectroscopy were used to analyze the produced AuNPs. The findings demonstrated that the AuNPs were spherical in shape with a diameter between 9.7 and 31 nm. Dermatophyte isolates were obtained from patients and identified by means of polymerase chain reaction (PCR), macroscopic and microscopic examination, and other methods. Some of the isolates were Microsporum canis, Trichophyton rubrum, and Trichophyton mentagrophytes.